2012
DOI: 10.1175/mwr-d-11-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

Subkilometer Simulation of a Torrential-Rain-Producing Mesoscale Convective System in East China. Part I: Model Verification and Convective Organization

Abstract: A nocturnal torrential-rain-producing mesoscale convective system (MCS) occurring during the mei-yu season of July 2003 in east China is studied using conventional observations, surface mesoanalysis, satellite and radar data, and a 24-h multinested model simulation with the finest grid spacing of 444 m. Observational analyses reveal the presence of several larger-scale conditions that were favorable for the development of the MCS, including mei-yu frontal lifting, moderate cold advection aloft and a moist mons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…However, toward lower latitudes such as the subtropics and tropics, the environments may be less conducive to cold pool development (e.g., Tompkins, 2001). Some studies of extreme rainfall events in South China and Taiwan have shown that surface-based cold air produced by previous convection that had dissipated for hours or even in the day before, when impinged by the moist monsoonal flow, in particular the lowlevel jet (LLJ), can act to trigger new convection in succession (e.g., Zhang and Zhang, 2012;Xu et al, 2012;C.-C. Wang et al, 2014a;Luo et al, 2014). Such influences of "cold domes," however, are different from the lifting at gust fronts produced by coexisting, dissipating cells or those that had just dissipated, and the induced MCSs may be less organized if a linear forcing such as a front or low-level convergence zone is absent (e.g., Xu et al, 2012;C.-C. Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…However, toward lower latitudes such as the subtropics and tropics, the environments may be less conducive to cold pool development (e.g., Tompkins, 2001). Some studies of extreme rainfall events in South China and Taiwan have shown that surface-based cold air produced by previous convection that had dissipated for hours or even in the day before, when impinged by the moist monsoonal flow, in particular the lowlevel jet (LLJ), can act to trigger new convection in succession (e.g., Zhang and Zhang, 2012;Xu et al, 2012;C.-C. Wang et al, 2014a;Luo et al, 2014). Such influences of "cold domes," however, are different from the lifting at gust fronts produced by coexisting, dissipating cells or those that had just dissipated, and the induced MCSs may be less organized if a linear forcing such as a front or low-level convergence zone is absent (e.g., Xu et al, 2012;C.-C. Wang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It is located in the extratropical region of east China, simultaneously affected by the subtropical and mid-to high-latitude large-scale systems during summer months ). The summer rainfall over this region is mostly caused by the mei-yu front, low pressure systems (e.g., southwest vortex), and mesoscale convective systems (MCSs) (Zhu et al 2000;Jiao et al 2004;Liu et al 2008;Zhang and Zhang 2012). The mei-yu front is characterized by weak temperature gradients but high equivalent potential temperature u e gradients due to the strong meridional moisture contrast.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, individual rainfall events are often seen being associated with frequently traveling synoptic-scale weather systems in midlatitudes (Jiao et al 2004;Qian et al 2004;Zhang and Zhang 2012). These weather systems can also be thought of as being a succession of synoptic-time-scale (3-8 days) disturbances (i.e., cyclonic and anticyclonic anomalies) in the atmospheric circulations (Lau and Lau 1990;Berry et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The northwesterly flow and southwesterly jet were separated by a shallow trough at 500 hPa, which showed up as a low vortex at 700 hPa but was invisible at 250 hPa. Associated with this shallow trough at 850 hPa ( Figure 2d) was a clear wind shift line from the southwest to northeast, which was almost collocated Atmosphere 2018, 9, 183 4 of 24 with the surface Meiyu front position, which can be roughly represented as 345 K equivalent potential temperature (θ e ) [5] (red dashed line).…”
Section: Overview Of the Iop-8 Casementioning
confidence: 97%
“…A deep understanding of the formation and evolution of these MCSs can help us better predict heavy rainfall and severe flooding in the Meiyu season. There have been many studies on the Meiyu frontal system and associated MCSs and heavy precipitation, including studies on the effects of the East Asian summer monsoon [3], large-scale moisture transport by the low-level jet (LLJ) typically found south of the Meiyu front [4][5][6], the eastward propagation of MCSs or mesoscale vortices along the Meiyu front [7,8], and diurnal cycle of precipitation [9][10][11][12]. The initiation of convective cells within the Meiyu frontal system that organizes into MCSs has been little studied, however.…”
Section: Introductionmentioning
confidence: 99%